Establishment and clinical application of a droplet digital PCR method for the detection of Edwardsiella tarda - Li, Min; Li, Xiaojun; Ye, Yifei; Yin, Jinfang; Mo, Zuanlan; Xie, Haiyan; Zhu, Yanqiu; Zhong, Liangning; Zhang, Xianpeng; Bi, Junlong (Frontiers in Veterinary Science, 2024)
Edwardsiella tarda (E. tarda) can infect humans and a variety of animals, including fish, amphibians, reptiles, birds, and mammals. However, a more highly sensitive, specific, and repeatable test for its detection is lacking. The objective of this study was to develop a highly sensitive, specific, and repeatable droplet digital polymerase chain reaction (ddPCR)-based method for the quantitative detection of E. tarda. The gyrB gene was selected as the target gene, and primers and probe were designed and synthesized. Using E. tarda genomic DNA as templates, the reaction method was optimized to establish a linear relationship with real-time PCR detection methods. The sensitivity, specificity, and repeatability of the method were analyzed, and clinical samples were tested. When the primer and probe concentrations were 900 and 300 nM, respectively, and the annealing temperature was 57°C, the efficiency of the ddPCR amplification reaction was highest and the boundary between positive and negative droplet distribution was clearest. The sensitivity was high, with detection limit being as low as 0.56 copies·μL−1; additionally, and a good linear relationship (R2 = 0.9962) between ddPCR and real-time PCR detection, within the range of 1–25,000 copies·μL−1, was evident. The repeatability was good, with a detection coefficient of variation of 2.74%. There was no cross-reactivity with 15 other common pathogenic microorganisms in aquatic animals (Streptococcus agalactiae, Streptococcus iniae, Streptococcus suis type 2, Nocardia seriolae, Vibrio parahaemolyticus, Aeromonas sobria, red sea bream iridovirus, decapod iridescent virus 1, enterocytozoon hepatopenaei, carp edema virus, Koi herpesvirus, goldfish hematopoietic necrosis virus, tilapia lake virus, viral nervous necrosis virus, or grass carp reovirus) in positive samples. Among the 48 clinical samples, including Bahaba taipingensis and its live food fish, pond water samples, and routine monitoring samples (Koi), 21 were positive for E. tarda, consistent with the bacterial isolation and identification results. The E. tarda ddPCR detection method has high specificity, sensitivity, and repeatability, can more accurately quantify E. tarda, and provides a useful reference for research related to this bacterium.